Tubercular arthritis of the elbow mimicking as a neoplasm: a case report and literature review - S., Ankitha K.; J., Ramesh L.; Krishna J. B., Vadhiraj; D., Karthik (International Journal of Research in Orthopaedics, 2024)
Tuberculous arthritis of the elbow joint is rare. A 38-year-old male patient presented with swelling, pain, and deformity of the elbow. The symptoms first appeared one year ago; he was clinic-radiologically evaluated and diagnosed with neoplasm. The patient underwent biopsy to confirm the diagnosis and was found to have tuberculous arthritis and was started on anti-tubercular treatment and underwent surgical debridement. Tuberculous arthritis usually presents with chronic arthritis. However, it can also present in patients with septic arthritis. If untreated, it can cause joint destruction. Hence, early diagnosis and treatment is important.